Percepciones sobre el tránsito a modalidades de enseñanza no presenciales. Un estudio exploratorio entre docentes de educación pública básica en la ciudad de Guadalajara, México - Chávez Palencia, Talía (2021)
The aim of this exploratory study, ran in Guadalajara city, Mexico, is to identify, among public education teachers, about the migration process to non presential teaching modalities. The methodological goal was to provide a solid and instantaneous cut in the middle of the experience of these teachers to get the opportunity to compare, in the long term, the evolution of those perceptions.